Individual muscle use in hamstring exercises by soccer players assessed using functional MRI - Fernandez-Gonzalo, R.; Tesch, P. A.; Linnehan, R. M.; Kreider, R. B.; Di Salvo, V.; Suarez-Arrones, L.; Alomar, X.; Mendez-Villanueva, A.; Rodas, G. (International Journal of Sports Medicine, 2016)
This study used functional magnetic resonance imaging (fMRI) to compare individual muscle use in exercises aimed at preventing hamstring injuries. Thirty-six professional soccer players were randomized into 4 groups, each performing either Nordic hamstring, flywheel leg curl, Russian belt or conic-pulley exercise. MRIs were performed before and immediately after a bout of 4 sets of 8 repetitions. Pre-post exercise differences in contrast shift (T2) were analyzed for the long (BFLh) and short head (BFSh) of biceps femoris, semitendinosus (ST), semimembranosus (SM) and gracilis (GR) muscles. Flywheel leg curl increased (P<0.001) T2 of GR (95%), ST (65%), BFSh (51%) and BFLh (14%). After the Nordic hamstring, GR (39%), ST (16%) and BFSh (14%) showed increased T2 (P<0.001). Russian belt and conic-pulley exercise produced subtle (P<0.02) T2 increases of ST (9 and 6%, respectively) and BFLh (7 and 6%, respectively). Russian belt increased T2 of SM (7%). Among exercises examined, flywheel leg curl showed the most substantial hamstring and GR muscle use. However, no single exercise executed was able to increase T2 of all hamstring and synergist muscles analyzed. It is therefore suggested that multiple exercises must be carried out to bring in, and fully activate all knee flexors and hip extensors.